2021
DOI: 10.1111/mmi.14669
|View full text |Cite
|
Sign up to set email alerts
|

σE controlled regulation of porin OmpU in Vibrio cholerae

Abstract: Bile resistance is essential for enteric pathogens, as exemplified by Vibrio cholerae, the causative agent of cholera. The outer membrane porin OmpU confers bacterial survival and colonization advantages in the presence of host‐derived antimicrobial peptides as well as bile. Expression of ompU is controlled by the virulence regulator ToxR. rpoE knockouts are accompanied by suppressor mutations causing ompU downregulation. Therefore, OmpU constitutes an intersection of the ToxR regulon and the σE‐pathway in V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…OmpU is well-conserved across Vibrio species and is the most abundant and best-studied OMP in V. cholerae ( 56 ). OmpU confers resistance to host-derived antimicrobial peptides, and bile connects envelope stress to activation of the σE pathway, facilitates the adhesion of V. cholerae to mammalian cells, and modulates host immune responses ( 45 , 57 59 ). We found that OmpU regulates biofilm matrix production, expanding the role OmpU plays in V. cholerae cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…OmpU is well-conserved across Vibrio species and is the most abundant and best-studied OMP in V. cholerae ( 56 ). OmpU confers resistance to host-derived antimicrobial peptides, and bile connects envelope stress to activation of the σE pathway, facilitates the adhesion of V. cholerae to mammalian cells, and modulates host immune responses ( 45 , 57 59 ). We found that OmpU regulates biofilm matrix production, expanding the role OmpU plays in V. cholerae cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…OmpU is widely present in NOVC [9,57,58] and should have the same response to the presence of bile. Due to its smaller channel size which prevents the influx of bile salts into the bacterial cell, the porin OmpU will be replaced instead of a larger channel porin such as OmpT [45,59].…”
Section: Outer Membrane Protein (Omp)mentioning
confidence: 99%